Effect of Human Amnion Epithelial Cells on the Acute Inflammatory Response in Fetal Sheep - Westover, Alana; Melville, Jacqueline M.; McDonald, Courtney; Lim, Rebecca; Jenkin, Graham; Wallace, Euan M.; Moss, Timothy J. (Frontiers in Physiology, 2017)
Intra-amniotic (IA) lipopolysaccharide (LPS) injection in sheep induces inflammation in the fetus. Human amnion epithelial cells (hAECs) moderate the effect of IA LPS on fetal development, but their influence on the acute inflammatory response to IA LPS is unknown. We aimed to determine the effects of hAECs on the acute fetal inflammatory response to IA LPS. After surgical instrumentation at 116 days’ gestation (d) ewes were randomised to 1 of 4 groups at 123 d: IA LPS (10 mg) and intravenous (IV) saline (n = 8), IA LPS and IV hAECs (n = 6), IA saline and IV saline (n = 5) or IA saline and IV hAECs (n = 5). IV injections were administered immediately after IA injections. Serial fetal blood samples were collected. At 125 d, placental, fetal lung and liver samples were collected. IA LPS increased inflammatory cell recruitment in the placenta and lungs, increased IL-1β and IL-8 mRNA levels in the lungs and increased serum amyloid A3 (SAA3) and C-reactive protein (CRP) mRNA levels in the liver. IV hAECs reduced fetal lung inflammatory cell recruitment but did not otherwise alter indices of placental, fetal lung or liver inflammation. The acute fetal inflammatory response to IA LPS is not substantially altered by IV hAEC treatment.